The influence of testosterone on the risk of cardiovascular events after percutaneous coronary intervention - Chiang, Cheng-Hung; Hung, Wan-Ting; Liu, En-Shao; Yang, Tse-Hsuan; Cheng, Chin-Chang; Huang, Wei-Chun; Mar, Guang-Yuan; Kuo, Feng-Yu (Frontiers in Cardiovascular Medicine, 2022)
Methods Between 2015 and 2018, 580 men undergoing PCI at a tertiary referral hospital were divided into low (<3.25 ng/mL) and normal (≥3.25 ng/mL) testosterone groups. Major adverse cardiovascular event (MACE) was defined as the composite outcome of CV death, myocardial infarction, and target lesion revascularization/target vessel revascularization (TLR/TVR) during up to 48 months follow-up after PCI. Results There were 111 and 469 patients in the low and normal testosterone groups, respectively, with the overall MACE rate of the former being higher than the latter (26.13% vs. 13.01%, p = 0.0006). Moreover, the overall TLR/TVR (20.72% vs. 11.73%, p = 0.0125) and myocardial infarction (3.6% vs. 0.85%, p = 0.0255) rates were significantly higher in those with low serum testosterone who also had a shorter average event-free survival analysis of MACE (25.22 ± 0.88 months) than those with normal testosterone levels (35.09 ± 0.47 months, log-rank p = 0.0004). Multiple logistic regression demonstrated an association between low serum testosterone (<3.25 ng/mL) and a higher MACE rate [odds ratio: 2.06, 95% confidence interval (CI) 1.21–3.51, p = 0.0081]. After adjusting for variables in a Cox regression model, hazard ratios (HRs) for MACE (HR: 1.88, 95% CI: 1.20–2.95, p = 0.0058) and TLR/TVR (HR: 1.73, 95% CI: 1.06–2.83, p = 0.0290) rates were higher in the low testosterone group than those in the normal testosterone group. Conclusion Low serum testosterone concentrations were associated with a higher risk of MACE and TLR/TVR after PCI than those with normal testosterone levels.